Development, delivery and evaluation of a team building project. Issue 1 (28th January 2014) - Ellis, Michelle; Kell, Billie
Abstract : Purpose: – The purpose of this paper is to illustrate the design, development, delivery and evaluation of a customised team building project on a paediatric unit. Design/methodology/approach: – The project content was tailored to meet the developmental needs of the staff working within the units, incorporating both soft and hard leadership approaches. A personal self development approach was used, and how this could enhance team working. Theory was embedded using innovative approaches that enabled practical application facilitating both surface and deep learning. Findings: – All staff participated and found themselves to have significantly developed both as individuals and as a team. They also identified the support required from management in order to fulfil their potential and to work effectively as a team. The teams have since completion of the project been more cohesive, are working more effectively and patient care has improved. Practical implications: – The project demonstrated how externally developed team building projects can be an effective approach to team building and leadership skill set acquisition, which can then be utilised in the practice arena. Originality/value: – Utilisation of a person centred approach to team building enables the individual to develop both as an individual and as a team – allowing them to contribute at a higher level.